Heart rate variability, serum cortisol levels and temperament in a sample of workers exposed to occupational stress: a preliminary report. Issue 3 (16th March 2023) - Buselli, Rodolfo; Veltri, Antonello; Corsi, Martina; Marino, Riccardo; Necciari, Gabriele; Baldanzi, Sigrid; Chiumiento, Martina; Del Lupo, Elena; Foddis, Rudy; Caldi, Fabrizio; Kozakova, Michaela; Guglielmi, Giovanni; et al.
ABSTRACT: Work-related stress is an emerging risk for psychiatric occupational disorders including Adjustment Disorders (AD). The aim of this study was to investigate in workers exposed to occupational stress suffering from AD about putative indices of stress and mental health resilience such as serum cortisol (seC) levels, Heart Rate Variability (HRV) and affective temperaments. We consecutively recruited 15 male and 15 female AD patients between workers evaluated for occupational stress at an Italian Occupational Medicine Unit. SeC levels were measured by specific immunoassay. HRV indices were recorded using Task Force® Monitor system (CNSystems, Graz, Austria). Specific questionnaires were used to measure perceived and occupational stress, psychopathological symptoms and temperament. Women presented higher levels of occupational stress, higher High-Frequency HRV (HF-HRV) and lower Low-Frequency HRV (LF-HRV) than men. SeC levels were positively correlated with LF-HRV values and negatively with HF-HRV values. The LF/HF ratio resulted to be inversely correlated with the score of Harm Avoidance temperament dimension and directly with the score of Reward Dependence temperament dimension. In conclusion, in AD patients exposed to occupational stress high seC levels and reward dependence appear to be associated with a pattern of HRV reflecting less mental health resilience.